2010
DOI: 10.1007/s11357-010-9159-3
|View full text |Cite
|
Sign up to set email alerts
|

How pleiotropic genetics of the musculoskeletal system can inform genomics and phenomics of aging

Abstract: Genetic study can provide insight into the biologic mechanisms underlying inter-individual differences in susceptibility to (or resistance to) organisms' aging. Recent advances in molecular genetics and genetic epidemiology provide the necessary tools to perform a study of the genetic sources of biological aging. However, to be successful, the genetic study of a complex condition requires a heritable phenotype to be developed and validated. Genome-wide association studies offer an unbiased approach to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 164 publications
(160 reference statements)
1
12
0
1
Order By: Relevance
“…These novel findings suggest that, although the klotho gene is a susceptibility gene for reduced BMD and lower serum klotho (<575 pg/mL) is related to greater declines in grip strength and higher disability, klotho blood levels were unrelated to bone loss or fracture risk in older adults. A possible explanation for the lack of association is the pleotropic function of the klotho gene . The transmembrane form of klotho, not measured in our study, is the bone‐derived hormone which is thought to be involved in bone regulation because of its coupling with FGF‐23.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These novel findings suggest that, although the klotho gene is a susceptibility gene for reduced BMD and lower serum klotho (<575 pg/mL) is related to greater declines in grip strength and higher disability, klotho blood levels were unrelated to bone loss or fracture risk in older adults. A possible explanation for the lack of association is the pleotropic function of the klotho gene . The transmembrane form of klotho, not measured in our study, is the bone‐derived hormone which is thought to be involved in bone regulation because of its coupling with FGF‐23.…”
Section: Discussionmentioning
confidence: 69%
“…A possible explanation for the lack of association is the pleotropic function of the klotho gene. 16 The transmembrane form of klotho, not measured in our study, is the bone-derived hormone which is thought to be involved in bone regulation because of its coupling with FGF-23. However, this form cannot be readily measured.…”
Section: Discussionmentioning
confidence: 74%
“…Phenome-wide association studies (PheWAS) studies aim to understand the role of a genetic variant identified from genome-wide association studies (GWAS) in increasing or decreasing the likelihood of observing other diseases in a case-control cohort. PheWAS studies are now revealing the molecular architecture of the pleiotropic nature of genetic variants in mediating multiple diseases 1,8 .…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming apparent that there are several genes involved in the genetic control of maturation, development, and decline of musculoskeletal systems [179181]. The heritability of lean mass, measured with DXA, has been estimated to vary between 56% and 84% [182] as well as those of bone strength, measured with section modulus of femoral neck, has been reported to be 40 to 55% [183].…”
Section: Evidence For Bone-muscle Interactionmentioning
confidence: 99%